IMPLEMENTASI KEBIJAKAN PENDIDIKAN TENTANG DEEP LEARNING - Aida Cahya Dwika Ramadhanti; Evy Ramadina; Cyntia Nur Azizah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The development of the digital era is pushing the world of education to provide a more meaningful learning process tailored to students' needs. One approach deemed capable of addressing this challenge is deep learning, which emphasizes not only in-depth understanding of the material but also fosters character, creativity, and critical thinking skills. This study aims to examine how implementation of education policies in Indonesia about deep learning, particularly as outlined in Permendikdasmen No. 13 of 2025. This research used descriptive qualitative methods combined with a literature review that collected various sources of literature, such as journals, books, and documents relevant to the research. The results of the study indicate that the government has provided fairly strong regulations for the implementation of deep learning. However, its implementation in schools still faces various obstacles, such as limited teacher competency, a lack of technological resources, and a learning culture that is still results-oriented. These findings confirm that the success of deep learning depends not only on the curriculum but also on the readiness and support of all educational components. Keywords: Policy, Education Policy, Deep Learning